The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/1412696
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Promotes Cardiomyocyte Proliferation and Heart Regeneration via ROS Scavenging

Abstract: Neonatal mouse hearts can regenerate completely in 21 days after cardiac injury, providing an ideal model to exploring heart regenerative therapeutic targets. The oxidative damage by Reactive Oxygen Species (ROS) is one of the critical reasons for the cell cycle arrest of cardiomyocytes (CMs), which cause mouse hearts losing the capacity to regenerate in 7 days or shorter after birth. As an antioxidant, hydrogen sulfide (H2S) plays a protective role in a variety of diseases by scavenging ROS produced during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…H 2 S is endogenously produced in the human body agent and participates in multiple physiologic processes and diseases [ 84 ]. In particular, it exhibits cardioprotective effects in the infarcted hearts [ 85 ]. Miao and colleagues showed that these protective effects were partially mediated by M2 macrophage activation [ 83 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…H 2 S is endogenously produced in the human body agent and participates in multiple physiologic processes and diseases [ 84 ]. In particular, it exhibits cardioprotective effects in the infarcted hearts [ 85 ]. Miao and colleagues showed that these protective effects were partially mediated by M2 macrophage activation [ 83 ].…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…These include genes encoding ETC components and ROS eliminator that protect cells from ROS damage and promote cardiomyocyte regeneration (84,103). Pei et al (104) confirmed that hydrogen sulfide (H2S) could scavenge ROS, and hence, cardiomyocytes could re-enter the proliferation cycle. Researchers used propargylglycine (PAG) to inhibit H2S synthesis and found that it promoted the deposition of ROS in the murine neonatal heart and inhibited proliferation of cardiomyocytes (104).…”
Section: Tricarboxylic Acid Cycle Metabolites and Cardiac Regenerationmentioning
confidence: 99%
“…Even in basal conditions, aerobic metabolism involves ROS production, thus making O 2 •− and H 2 O 2 physiological intracellular metabolites. In low quantities, ROS act as signalling molecules involved in different pathways, such as cell proliferation, apoptosis and gene expression [ 291 , 292 ]. However, the fact that an important increase in oxidants could target almost all substrates implies the impairment and alteration of all biomolecules, resulting in cell damage and death [ 293 , 294 ].…”
Section: Mechanisms Involved In Fibrosis Progressionmentioning
confidence: 99%